Morphological and phylogenetic evidence supports four new species and one new record of Entoloma (Entolomataceae, Agaricales) from Northeast China - Zhang, Tian-Yu; Bau, Tolgor (Phytotaxa, 2026)
Based on morphological examination and phylogenetic analyses of ITS and nrLSU sequences, four new species and one new record of Entoloma were identified from Jilin Province, China. The four new species are described as Entoloma hongshiense and E. bulbocystum (subgen. Leptonia), E. cirratum (subgen. Pouzarella), and E. changbaiense (subgen. Cyanula). Additionally, E. roseoflavum (subgen. Cyanula) is reported as a new geographical record for China, accompanied by its first DNA sequence data. Detailed morphological descriptions, line drawings, and phylogenetic trees are presented to support the establishment of these taxa.